Lâminas de irrigação no desenvolvimento e produção do feijão-caupi na região central do Rio Grande do Sul, Brasil - Dauala, Gonçalves Albino (2016)
The yield of cowpea in Brazil is still low due to inadequate supply of water by rain and irrigation during the vegetative and reproductive stages. One of the alternatives to improve yield is conducting regional studies with different cultivars and adequate irrigation management. Because that, was conducted the field experiment from december of 2014 to march of 2015 in the experimental area of the Polytechnic School of the Federal University of Santa Maria, in dystrophic red argissolo, with a loam texture to evaluate the effect of the application of supplemental irrigation levels by drip on growth parameter, dry grain yield and its components in cowpea cultivars at conditions of Santa Maria, RS. The treatments consisted of the combination of five irrigation levels (0, 25, 50, 75 and 100% of crop evapotranspiration) and two cultivars of cowpea (BRS Potengi and BRS Novaera) arranged in a randomized blocks design experimental spli-plots and four replications, where irrigation levels were distributed in the main-plots and cultivars in the sub-plots. Application of the treatments stared at 31 days after seeding (DAS). Evaluated the plant height, leaf area index, and dry mass of the aerial part (MSPA) after 38, 45 and 52 DAS. Also evaluated the production components: number of pods per plant, pod compliance, number of grain per pod, weight of hundred (100) grains and grain yield. To study conditions there was no significant interaction between treatments for any of the variables. The Irrigation levels influenced only in the MSPA to 45 DAS in both cultivars. The cultivars showed significant differences between them in all production components, grain yield, MSPA for the evaluated days and leaf area index only 45 and 52 DAS. For the study conditions, was not possible to determine the irrigation levels that allow achieving maximum grain yield for each cultivar due to the occurrence of rainfall during the experiment, was above the climatological normal from the site of the experiment. So, being the supplementary irrigation is not recommended. However, it is recommended to study the influence of irrigation in years when rainfall is below the climatological normal. The BRS Novaera had higher grain yield (1559 kg ha-1) compared BRS Potengi (1505 kg ha-1).